C-5a-substituted validamine type glycosidase inhibitors. (22nd February 2017) - Schalli, Michael; Wolfsgruber, Andreas; Gonzalez Santana, Andres; Tysoe, Christina; Fischer, Roland; Stütz, Arnold E.; Thonhofer, Martin; Withers, Stephen G.
Abstract: A series of N -alkyl derivatives of the D-galactosidase inhibitor 1, 4-di- epi -validamine featuring lipophilic substituents at position C-5a was prepared and screened for their glycosidase inhibitory properties. Products turned out selective for β-galactosidases as well as β-glucosidases. Graphical abstract: Highlights: A simple route enables access to C-5a-hydroxylated derivatives of 1, 4-di- epi -validamine. Regioselective derivatization with a range of isocyanates provides one-step access to lipophilic analogs. Additional modifications are available by simple 1- N -alkylation. Final products are inhibitors of β-galactosidases.